Psikologi Islam Ibn Miskawaih Dalam Rehabilitasi Penyakit Mental Manusia - Nurul Khair; Kirana Fatmawati (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2022)
This article aims to examine the urgency of Ibn Miskawaih's Islamic psychology in rehabilitating human mental illness by referring to one of his magnumopuses entitled Tahdzīb Al-Akhlāq and several studies on his frame of mind. By using descriptive analysis, it is concluded that Ibn Miskawaih's Islamic psychology is studied through the discourse of al-quwwah al-ghadābiyyah which affects human feelings and thoughts as an indicator of the creation of suffering, depression, and sadness. In order to overcome the mental illness faced by modern humans, Ibn Miskawaih through his philosophical discourse on the soul views the problems of suffering, depression, and sadness based on the anxiety of the human soul in thinking and stimulating everything in reality. The soul is the essence of human existence that affects human actions, thoughts, and feelings so that individuals must practice the perfection of their essence through al-quwwah an-natiqah. In addition to offering a philosophical discourse on the soul as a mental illness rehabilitation process, Ibn Miskawaih's paradigm also responds to the views of western psychologists, such as Aaron Beck and Sigmund Freud who assess mental illness can be treated through social relationships. As a result, human mental rehabilitation is only studied materially, without seeing the essence that is seen as the core of human existence in reality. The result of this paper is to perfect the offer of western psychologists in the discourse of science through Ibn Miskawaih's Islamic psychology.